Decomposition Analysis of Energy Consumption in Pakistan for the Period 1990-2013 - Faisal Jamil; Arbab Shahzad (NUST Journal of Social Sciences and Humanities, 2021)
The final energy consumption in Pakistan has doubled during the last two decades. Investigating the factors responsible for changes in energy use is important for future projections. Decomposition techniques enable us to quantify the contributing factors in aggregate energy change. This study attempts to investigate the factors behind the aggregate change in energy consumption over the period 1990-2013 using Logarithmic Mean Divisia Index (LMDI) decomposition technique. LMDI decomposes the overall change in energy use into three effects namely, activity, structural, and intensity effects. Results of the study suggest that observed increase in Pakistan’s energy consumption is primarily due to the activity and structural effects. The energy intensity of overall economy has decreased showing an increase in energy efficiency, though at a decreasing rate over time. The quantification of energy imports based on projections shows that Pakistan may face serious fiscal challenge by 2025 due to extremely large energy import bill and possible energy price shocks. There is a need to put efforts towards reducing the gap between energy supply and demand, diversifying domestic energy production including increased reliance on renewables, efforts towards energy and environment conservation, and efficient use of available resources.